Immunotherapy for glioma: Current management and future application - Xu, Shengchao; Tang, Lu; Li, Xizhe; Fan, Fan; Liu, Zhixiong (Cancer letters, 2020)
Gliomas are intrinsic brain tumors that originate from neuroglial progenitor cells. Conventional therapies, including surgery, chemotherapy, and radiotherapy, have achieved limited improvements in the prognosis of glioma patients. Immunotherapy, a revolution in cancer treatment, has become a promising strategy with the ability to penetrate the blood-brain barrier since the pioneering discovery of lymphatics in the central nervous system. Here we detail the current management of gliomas and previous studies assessing different immunotherapies in gliomas, despite the fact that the associated clinical trials have not been completed yet. Moreover, several drugs that have undergone clinical trials are listed as novel strategies for future application; however, these clinical trials have indicated limited efficacy in glioma. Therefore, additional studies are warranted to evaluate novel therapeutic approaches in glioma treatment. •Current management of glioma is limited and cannot reach an optimal remission.•Immune checkpoint inhibitors and CAR-T therapy exhibit promising therapeutic activities as immunotherapies.•Combination of oncolytic virus, dendritic vaccines, and immune checkpoint inhibitors has synergistic effect killing tumors.•Novel CAR-T strategies and bi-specific antibodies are developed in cancer treatment.•Combination and personalized therapy take a crucial place in future application.